Enforcement Of Criminal Acts Of Violence Threats On Social Media Based On Article 29 Paragraph (1) Of The Information And Electronic Transactions Law - Yurike Revina Maharani; Yudi Fahrian; Suryani Yusi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study discusses the law enforcement of criminal acts of threats of violence on social media based on Article 29 Paragraph (1) of Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE). The purpose of this research is to identify the legal implications of threats of violence through electronic media and the factors hindering law enforcement. The research method used is normative legal research with a statute approach and a conceptual approach. The results indicate that Article 29 Paragraph (1) of the ITE Law has expanded protection for victims by clarifying the phrase